2022
DOI: 10.1093/eurheartj/ehac544.1464
|View full text |Cite
|
Sign up to set email alerts
|

The role of peak NT-proBNP/peak cardiac troponin T ratio obtained within 3 days of admission to discriminate Takotsubo from acute coronary syndrome

Abstract: Background Takotsubo syndrome (TS) is not usually diagnosed until a patient with suspected acute coronary syndrome (ACS) is found to have no hemodynamically significant lesions on coronary angiography (CA). Purpose We explored whether a cardiac biomarker profile can contribute to early diagnosis of TS, which could be useful when CA is either not available or does not provide a definitive diagnosis. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…[ 24 ] For the early identification and diagnosis of patients with ACS, an increasing number of studies have focused on the use of biomarkers to make judgments, among which immediate measurement of cardiac troponin is a common method. [ 25 , 26 ] Some studies have shown that the heart fatty acid binding protein also has potential diagnostic value in the early period after the onset of ACS symptoms, [ 27 , 28 ] but further validation studies on new predictors are needed to identify and diagnose patients as early as possible, and to take early interventions to improve therapeutic outcomes and survival rates. Percutaneous coronary intervention, as a special treatment modality, significantly solves the reperfusion situation of ACS patients, and its post-procedure care and recovery have also attracted much attention.…”
Section: Discussionmentioning
confidence: 99%
“…[ 24 ] For the early identification and diagnosis of patients with ACS, an increasing number of studies have focused on the use of biomarkers to make judgments, among which immediate measurement of cardiac troponin is a common method. [ 25 , 26 ] Some studies have shown that the heart fatty acid binding protein also has potential diagnostic value in the early period after the onset of ACS symptoms, [ 27 , 28 ] but further validation studies on new predictors are needed to identify and diagnose patients as early as possible, and to take early interventions to improve therapeutic outcomes and survival rates. Percutaneous coronary intervention, as a special treatment modality, significantly solves the reperfusion situation of ACS patients, and its post-procedure care and recovery have also attracted much attention.…”
Section: Discussionmentioning
confidence: 99%